3-dimensional porous NiCo2O4 nanocomposite as a high-rate capacity anode for lithium-ion batteries. (10th September 2015) - Mo, Yudi; Ru, Qiang; Song, Xiong; Hu, Shejun; Guo, Lingyun; Chen, Xiaoqiu
Graphical abstract: Highlights: D-glucose molecules as organic carbon source, have a crucial effect on the morphology and pore distribution of the synthetic products. Facile synthesis: solvothermal method. High rate capacity: 625 mAh g −1 at 4.4 C. Improved long-term cycling stability: 1389 mAh g −1 after 180 cycles at 0.55 C. Abstract: In this work, organic carbon modified NiCo2 O4 (NCO@C) nanocomposite with porous 3-dimensional (3D) structure was successfully synthesized by a facile hydrothermal method in D-glucose-mediated processes. A detailed research reveals that D-glucose molecules play an important role in the formation of the porous 3D structure and also provide a conductive carbon network within the NCO@C nanocomposite materials. Such a porous 3D interconnected carbonaceous nanostructure applied as electrode material for lithium-ion batteries (LIBs) shows that its reversible capacity, cycling stability, and rate capability are significantly enhanced in comparison with those of pure NiCo2 O4 (NCO) electrode. The as-prepared NCO@C composite electrode with porous 3D nanostructure displays a higher discharge specific capacity of 1389 mAh g −1 even after 180 cycles at a current rate of 0.55 C. Furthermore, this composite material also presents a high rate capacity, when the current rate gradually increases to 0.55 C, 1.1 C, 2.2 C, and 4.4 C, the reversible capacity can still render about 1082, 1029, 850, and 625 mAh g −1, respectively. The enhanced electrochemical performance indicated that the NCO@C nanocomposite might be a very promising candidate to replace conventional graphite-based anode materials for LIBs.